Utilization of Chat GPT Artificial Intelligence (AI) in Student’s Learning Experience Gen-Z Class - Zulfikasari, Sony; Sulistio, Basuki; Aprilianasari, Woro (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2024)
Technology presents data very quickly, if students do not get enough assistance from lecturers in analytical thinking, the students will present data without studying further or it will convince them that what is presented is justifiable. Lecturers need to understand the students' learning habit nowadays. The focus in this study is the usage of Chat GPT AI in Student Learning Experience in Gen-Z classroom. This study provides in-depth attention to educators, especially lecturers, so that they can adapt to Gen Z's learning experience tendencies and the latest developments in learning media to create the material. The method used in this study is descriptive quantitative with questionnaires distributed to students. The respondent in this study is 392 Gen Z students chosen with purposive random sampling. The use of Chat GPT AI is familiar to Gen-Z students. Therefore, they should double-check the results of Chat GPT so as not to make misinformation and they provide a complete understanding. Lecturers as facilitators in the classroom must be more careful in reviewing the assignments collected by students, so that lecturers can measure precisely that the assignments are the same as the level of student understanding. In addition, the lecturers should notice that the information presented is correct.